2021
DOI: 10.3390/nu13072303
|View full text |Cite
|
Sign up to set email alerts
|

Creatine Enhances the Effects of Cluster-Set Resistance Training on Lower-Limb Body Composition and Strength in Resistance-Trained Men: A Pilot Study

Abstract: Creatine monohydrate (CrM) supplementation has been shown to improve body composition and muscle strength when combined with resistance training (RT); however, no study has evaluated the combination of this nutritional strategy with cluster-set resistance training (CS-RT). The purpose of this pilot study was to evaluate the effects of CrM supplementation during a high-protein diet and a CS-RT program on lower-limb fat-free mass (LL-FFM) and muscular strength. Twenty-three resistance-trained men (>2 years of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 64 publications
0
20
0
1
Order By: Relevance
“…In the same line, Gonzalez-Hernández et al [16] showed that intra-set resting periods in between 15-30 s might be better from a hypertrophy point of view, given that a similar mechanical output could be obtained compared with more extended resting periods but with more emphasis on metabolic stress that could enhance the muscle growth stimuli. Additionally, we report that the application of creatine monohydrate in 3 RM protocols with 20 pauses would notably increase the fat-free mass and strength levels evaluated by MR [21].…”
Section: Cluster Sets and Muscle Hypertrophymentioning
confidence: 83%
“…In the same line, Gonzalez-Hernández et al [16] showed that intra-set resting periods in between 15-30 s might be better from a hypertrophy point of view, given that a similar mechanical output could be obtained compared with more extended resting periods but with more emphasis on metabolic stress that could enhance the muscle growth stimuli. Additionally, we report that the application of creatine monohydrate in 3 RM protocols with 20 pauses would notably increase the fat-free mass and strength levels evaluated by MR [21].…”
Section: Cluster Sets and Muscle Hypertrophymentioning
confidence: 83%
“…Studies such as those by Bonilla et al [ 5 ] and Mills et al [ 32 ] used similar variables to those in this study to determine what effect Cr supplements had on athletic performance. The results obtained in the present study are in line with those published in these two articles, with improvements being found in the 1RM squat, CMJ, and medicine ball throwing tests.…”
Section: Discussionmentioning
confidence: 99%
“…In muscles, ATP is used by the enzyme phosphorylcreatine kinase (CK) to convert Cr to Cr phosphate. This enzyme can reverse the reaction to obtain additional ATP, making Cr phosphate a temporary store of ATP under high energy demand conditions [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CK/PCr system can be enhanced through supplementation with creatine monohydrate (CrM), which is the most studied, safe, and effective nutritional supplement to optimize physical performance [ 5 , 6 , 7 , 8 ], with potential benefits in health and disease [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. It seems that the elevation of intracellular PCr concentration causes a greater capacity for phosphagens to contribute to energy metabolism, while working to reduce the accumulation of Pi and H + and improving Ca 2+ handling as important mediators of fatigability in young and older adults [ 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%